2021
DOI: 10.1111/all.14953
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term disruption of cytokine signalling networks is evident in patients who required hospitalization for SARS‐CoV‐2 infection

Abstract: T H 2-associated pathological immune activity that might underpin an increased risk of developing allergy or asthma? Clearly, the potential immune mechanisms underpinning the emerging post-COVID clinical entities will become increasingly more important to understand as the healthcare systems adapt to caring for large numbers of COVID-19 survivors during the coming months and years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 6 publications
1
22
0
2
Order By: Relevance
“…Persistent endothelial dysfunction may be responsible for the wide variation in symptoms reported [11][12][13]. There is also some evidence suggesting that altered inflammatory cytokine pathways may persist during convalescence [14].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent endothelial dysfunction may be responsible for the wide variation in symptoms reported [11][12][13]. There is also some evidence suggesting that altered inflammatory cytokine pathways may persist during convalescence [14].…”
Section: Introductionmentioning
confidence: 99%
“…6–8 Acute illness is associated with substantial immune activation 911 and central nervous system (CNS) dysfunction. 1116 A handful of studies have measured serum glial fibrillary acidic protein (GFAP), an intermediate filament protein found in the cytoskeleton of CNS astrocytes, 17 and neurofilament light chain (NfL), a cytoskeletal protein expressed in the axons of neurons 18 during acute COVID-19. 19–28 In some cases, higher levels of these markers were identified in patients with neurologic symptoms during acute infection; 2125 other studies have not identified such relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, TSLP levels were previously shown to be elevated in patients with long COVID, suggesting that long-term impacts of SARS-CoV-2 on epithelial cells should be examined in more detail, potentially guiding future therapeutic interventions. 36 While elevated proinflammatory cytokine levels are a common feature also associated with severe responses to other respiratory viruses such as influenza A(H1N1), the pattern of polyfunctional cytokine responses described in the current study seems to be specifically associated with severe COVID-19, potentially due to the broad infective capacity of SARS-CoV-2 to invade tissues and organs outside the respiratory tract. 37 , 38 …”
Section: Discussionmentioning
confidence: 53%